Associations of P Score With Real-World Survival Improvement Offered by Adjuvant Chemotherapy in Stage II Colon Cancer: A Large Population-Based Longitudinal Cohort Study - Liu, Qi; Shan, Zezhi; Luo, Dakui; Zhang, Sheng; Li, Qingguo; Li, Xinxiang (Frontiers in oncology, 2021)
Based on a prognostic scoring system ( score) proposed by us recently, this retrospective large population-based and propensity score-matched (PSM) study focused on predicting the survival benefit of adjuvant CT in stage II disease. Patients diagnosed with stage II colon cancer (N = 73397) were identified from the Surveillance, Epidemiology, and End Results database between January 1, 1988 and December 31, 2005 and divided into the CT and non-CT groups. PSM balanced the patient characteristics between the CT and non-CT groups. The magnitude of CSS improvement among patients treated with adjuvant CT was significantly associated with the P score, score 8 [hazard ratio (HR) = 0.580, 95% confidence interval (CI) = 0.323-1.040, P = 0.067] was associated with a much higher increased CSS benefit among patients treated with adjuvant CT as compared to score 2* (*, including scores 0, 1, and 2; HR = 1.338, 95% CI = 1.089-1.644, P = 0.006). High scores were demonstrated to be associated with superior survival benefit of adjuvant CT. Therapy decisions of adjuvant CT in stage II colon cancer could be tailored on the basis of tumor biology, patient characteristics and the score.